2020
DOI: 10.1002/biof.1699
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin as a modulator of skin aging and inflammation

Abstract: Luteolin belongs to the group of flavonoids and can be found in flowers, herbs, vegetables and spices. It plays an important role in defending plants, for example against UV radiation by partially absorbing UVA and UVB radiation. Thus, luteolin can also decrease adverse photobiological effects in the skin by acting as a first line of defense. Furthermore, anti-oxidative and anti-inflammatory activities of luteolin were described on keratinocytes and fibroblasts as well as on several immune cells (e.g., macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(153 citation statements)
references
References 95 publications
(206 reference statements)
3
148
0
2
Order By: Relevance
“…Flavones are one of the biggest families of flavonoids and their functions in plants include protection against UV radiation and oxidative stress, signaling, and interactions with other organisms [30,31]. In addition, both apigenins and luteolins are interesting medicinal compounds [30,32]. The flavones found in our study coincided with some of those previously found in M. polymorpha subsp.…”
Section: Phenolic Composition Of the Liverwort Samplessupporting
confidence: 87%
“…Flavones are one of the biggest families of flavonoids and their functions in plants include protection against UV radiation and oxidative stress, signaling, and interactions with other organisms [30,31]. In addition, both apigenins and luteolins are interesting medicinal compounds [30,32]. The flavones found in our study coincided with some of those previously found in M. polymorpha subsp.…”
Section: Phenolic Composition Of the Liverwort Samplessupporting
confidence: 87%
“…Recent research pointed out that luteolin might be a promising molecule for developing topic formulations and systemic agents against inflammatory skin diseases. It has also been suggested as a cancer chemopreventive agent [ 49 , 50 ]. In our study, luteolin was abundant in three high-quality foxtail millet varieties but absent in the other two varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Lut can stabilize the radical group by donating hydrogen/electron of C2–C3 double bond to radical and by blocking Fenton reaction using oxo group at C4 that binds transitional metal ions including iron and copper. These two structural features of Lut inhibit pro-oxidant enzymes such as xanthine oxidase, and induce antioxidant enzymes ( Gendrisch et al, 2021 ). In addition, Lut not only has its own antioxidant activity, but also interacts with other antioxidants such as vitamins and cellular redox system ( Gendrisch et al, 2021 ), indicating that Lut can synergistically enhance its antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…These two structural features of Lut inhibit pro-oxidant enzymes such as xanthine oxidase, and induce antioxidant enzymes ( Gendrisch et al, 2021 ). In addition, Lut not only has its own antioxidant activity, but also interacts with other antioxidants such as vitamins and cellular redox system ( Gendrisch et al, 2021 ), indicating that Lut can synergistically enhance its antioxidant properties. Furthermore, some flavonoids including quercetin, genistein, and catechin induce DNA damage by pro-oxidative effect resulting in mutagenic and carcinogenic activity ( Kawanishi et al, 2005 ; Gendrisch et al, 2021 ), but Lut has no report regarding these effects, suggesting that Lut can be expected as a comparatively safe antioxidant ( Yamashita et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%